2017
DOI: 10.1155/2017/7207983
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapy and Nutritional Supplements on Breast Cancer

Abstract: Breast cancer is the most frequent type of nonskin malignancy among women worldwide. In general, conventional cancer treatment options (i.e., surgery, radiotherapy, chemotherapy, biological therapy, and hormone therapy) are not completely effective. Recurrence and other pathologic situations are still an issue in breast cancer patients due to side effects, toxicity of drugs in normal cells, and aggressive behaviour of the tumours. From this point of view, breast cancer therapy and adjuvant methods represent a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 407 publications
(461 reference statements)
0
54
0
Order By: Relevance
“…However, the functional differences made by genomically heterogeneous triple-negative breast cancer cells to chemoresistance remain poorly understood [31]. Natural ingredients from plants are widely explored to identify their availability for application in patients with breast cancer as an adjuvant approach [32]. For example, curcumin, a bioactive ingredient of the plant Curcuma longa, exerts an inhibitory effect on triple-negative MDA-MB-231 breast cancer cells through upregulation of p21 protein expression and enhancement of the Bax-to-Bcl-2 ratio [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, the functional differences made by genomically heterogeneous triple-negative breast cancer cells to chemoresistance remain poorly understood [31]. Natural ingredients from plants are widely explored to identify their availability for application in patients with breast cancer as an adjuvant approach [32]. For example, curcumin, a bioactive ingredient of the plant Curcuma longa, exerts an inhibitory effect on triple-negative MDA-MB-231 breast cancer cells through upregulation of p21 protein expression and enhancement of the Bax-to-Bcl-2 ratio [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies reported the antioxidant, anti-neoplastic and immunomodulant activities of the alkaloids isolated from the cat's claw [36][37][38]. For instance, Lopes et al [39] revealed that U. tomentosa extract encourages the myeloid precursor's proliferation by increasing serum colony-stimulating growth factors (CSFs). Moreover, in vivo studies demonstrated the effectiveness of aqueous U. tomentosa extract on leukocyte counts in healthy animals and doxorubicin-induced neutropenia [23,40,41].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Theoretically, it was believed that POA isolated from cat's claw possesses an immunostimulatory effect, therefore, it is contraindicated to be used with immunosuppressant drugs including cyclosporine, azathioprine, daclizumab, basiliximab, mycophenolate, muromonab-CD3, tacrolimus, sirolimus, corticosteroids, prednisone, or other chemotherapeutic drugs recommended for autoimmune disease treatment or after organ transplantation [39,62].…”
Section: Immunosuppressant Drugsmentioning
confidence: 99%
“…Ginseng is relatively nontoxic but in high doses (i.e., superior to 3 g ginseng root daily) can confer adverse symptoms such as insomnia, nervous excitation, headaches, and nausea. Ginseng may present steroid/hormone like effects, so in women who have breast or endometrial cancer special attention for its use is recommended (25).…”
Section: Single Herbssmentioning
confidence: 99%